2006
DOI: 10.1002/elan.200503473
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Biosensors Based on the Immobilization of Hemoglobin on Mesoporous Titania Electrodes

Abstract: A nanocrystalline TiO 2 film is an electrode material with large surface area which allows high levels of protein adsorption without loss of protein structure or activity. As an optically transparent semiconductor, titania can be used to carry out direct spectroelectrochemistry of proteins such as hemoglobin. We demonstrate that the high protein loading and the optical transparency and electrical conductivity of the Hb/TiO 2 films allow the optical and/or electrochemical sensing of nitric oxide. In particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…However, the charge for Hb adsorbed on the MPPA/Au surface was calculated to be 1.95 10 À5 C cm À2 by integrating the CV oxidation peak and using the real surface area of the bare Au electrode (0.0736 cm 2 ). This value is about ten times larger than the theoretical charge (Q* = 1.82 10 À6 C cm…”
Section: à2mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the charge for Hb adsorbed on the MPPA/Au surface was calculated to be 1.95 10 À5 C cm À2 by integrating the CV oxidation peak and using the real surface area of the bare Au electrode (0.0736 cm 2 ). This value is about ten times larger than the theoretical charge (Q* = 1.82 10 À6 C cm…”
Section: à2mentioning
confidence: 99%
“…[1] Among the proteins and enzymes containing heme groups, hemoglobin (Hb) is an ideal model molecule because of its known structure, commercial availability, and relatively high stability. [2] Nevertheless, facilitating electron transfer between the macromolecule Hb and electrodes is still challenging. Generally, inaccessibility of the heme group, buried in a large three-dimensional protein shell, and electrode passivation due to protein adsorption make it difficult to establish direct electron transfer between Hb and conventional electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the particle size and porosity in TiO 2 phytate films have been demonstrated to have a considerable effect on the adsorption and transport of proteins in the film by voltammetric methods [15]. Meanwhile, Hb has been entrapped in a TiO 2 sol-gel matrix or adsorbed on nanocrystalline TiO 2 films to construct amperometric H 2 O 2 biosensors [16], NO electrochemical biosensors [17], or amperometric antioxidant sensors [18]. Various types of TiO 2 materials such as highly ordered mesoporous TiO 2 [19], TiO 2 nanotubes [20,21], TiO 2 nanorods [22], and TiO 2 whisker [23] have been prepared for hemoglobin immobilization and utilized for the study of direct electron transfer of Hb.…”
Section: Introductionmentioning
confidence: 99%
“…Salimi [18] et al has reported the fabrication of glucose biosensor by immobilizing GOx into a sol-gel composite at the surface of a basal plane pyrolytic graphite electrode modified with CNT. Other nanomaterials, such as nickel oxide [19], titanium oxide [20,21], tungsten oxide [22], iron oxide [23] manganese oxide [24], and zirconium oxide [25] have been used successfully for immobilization of enzymes and proteins. Those studies have showed that the new metal oxide NPs exhibit high biocompatibility, high adsorption ability and little harm to the biological activity of redox proteins.…”
Section: Introductionmentioning
confidence: 99%